CONVERGENCE OF CARBON PRICING POLICY AS A CLIMATE CHANGE SOLUTION TO RECOVERY ENVIRONMENTAL DAMAGE IN INDONESIA - Nasution, Faradila Umaya (NOMOI Law Review, 2024)
The carbon pricing refers to the costs imposed by the carbon tax on a company based on the amount of carbon as they emit. The government establishes carbon price policy through regulations and policies. In Indonesia, carbon prices are still being determined through theoretical methods. This research provides valuable insights for legal evaluation, indicating that environmental policies in Indonesia should prioritize the welfare of individuals affected by environmental pollution. Carbon pricing is expected to be a tool for controlling climate change in Indonesia and promoting the green economy concept by applying economic value